On the Efficacy of H2O2 or S2O82− at Promoting the Inactivation of a Consortium of Cyanobacteria and Bacteria in Algae-Laden Water - Javier Moreno-Andrés; Ignacio Rivas-Zaballos; Asunción Acevedo-Merino; Enrique Nebot (Microorganisms, 2022)
Harmful algal blooms in coastal areas can significantly impact a water source. Microorganisms such as cyanobacteria and associated pathogenic bacteria may endanger an ecosystem and human health by causing significant eco-hazards. This study assesses the efficacy of two different reagents, H2O2 and S2O82−, as (pre-)treatment options for algae-laden waters. Anabaena sp. and Vibrio alginolyticus have been selected as target microorganisms. With the objective of activating H2O2 or S2O82−, additional experiments have been performed with the presence of small amounts of iron (18 µmol/L). For the cyanobacterial case, H2O2-based processes demonstrate greater efficiency over that of S2O82−, as Anabaena sp. is particularly affected by H2O2, for which >90% of growth inhibition has been achieved with 0.088 mmol/L of H2O2 (at 72 h of exposure). The response of Anabaena sp. as a co-culture with V. alginolyticus implies the use of major H2O2 amounts for its inactivation (0.29 mmol/L of H2O2), while the effects of H2O2/Fe(II) suggests an improvement of ~60% compared to single H2O2. These H2O2 doses are not sufficient for preventing the regrowth of V. alginolyticus after 24 h. The effects of S2O82− (+ Fe(II)) are moderate, reaching maximum inhibition growth of ~50% for Anabaena sp. at seven days of exposure. Nevertheless, doses of 3 mmol/L of S2O82− can prevent the regrowth of V. alginolyticus. These findings have implications for the mitigation of HABs but also for the associated bacteria that threaten many coastal ecosystems.